2019
DOI: 10.5455/javar.2019.f307
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance, metabolic and hematologic parameters of gestating nulliparous rabbit does according to dietary protein level

Abstract: Objective: This study aims at investigating the productive performance, metabolic, and hematological profiles of Algerian local rabbits does during their first pregnancy and according to dietary protein content. Materials and methods: A total of 52 nulliparous rabbit does, 3,116 ± 72.9 g live weight, were allocated individually to three groups (17/18 females per group) being on isoenergetic diets [2,600 kcal Digestible Energy (DE)/kg] that differ in their digestible pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…When compared to other rearing feeding programmes, this management achieved the best performance results during the first reproductive cycle. Finally, Saidj et al (2019) observed that, when increasing the crude protein (CP) content from 150 to 170 g/kg in diets with 10.9 MJ DE/kg, no significant differences were observed at metabolic level (glucose, urea, triglycerides total protein and blood cells counts) and in reproductive performance (female feed intake and live weight, as well as litter performance).…”
Section: Rearing Feeding Programmes: High-fibre Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to other rearing feeding programmes, this management achieved the best performance results during the first reproductive cycle. Finally, Saidj et al (2019) observed that, when increasing the crude protein (CP) content from 150 to 170 g/kg in diets with 10.9 MJ DE/kg, no significant differences were observed at metabolic level (glucose, urea, triglycerides total protein and blood cells counts) and in reproductive performance (female feed intake and live weight, as well as litter performance).…”
Section: Rearing Feeding Programmes: High-fibre Dietsmentioning
confidence: 99%
“…Figure 2: Meta-analysis on the effect of composition of the feed received during the rearing period on the conception rate in the first artificial insemination, stillborn ratio and feed intake during lactation of primiparous rabbit does. Built from literature (Xiccato et al, 1995;Nizza et al, 1997;Pascual et al, 2002;Quevedo et al, 2005;Arias-Álvarez et al, 2009;Rebollar et al, 2011;Martińez-Paredes et al, 2012, 2018Saidj et al, 2019). LW: liveweight.…”
Section: Rearing Feeding Programmes: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…Several research projects have been conducted in Algeria to improve the quality of rabbit feed for growing rabbits (Kadi, 2012;Guermah, 2016;Djellal, 2019) and for rabbits does (Saidj et al, 2016(Saidj et al, , 2019. The objective of the present work is to assess the effects of dietary restriction, by time-limited access to the feeders, on growth performance and carcass characteristics of growing rabbits issued from non-selected line of Algerian local populations.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated the characterization of the local rabbit population in Algeria since it is a popular population used by family farms with low sensitivity to heat (Ilès, 2017;Belabbas et al, 2019;Saidj et al, 2019). However, only a few studies have focused on the effect of heat stress on rabbits' production and productivity traits.…”
Section: Introductionmentioning
confidence: 99%